Effects of Laser Scanning Speed on Microstructure, Microhardness, and Corrosion Behavior of Laser Cladding Ni45 Coatings - Yanxin Qiao; Jie Huang; Ding Huang; Jian Chen; Wen Liu; Zhengbin Wang; Zheng Zhibin (Journal of Chemistry)
The effects of laser scanning speed on the microstructure, microhardness, and corrosion behavior of Ni45 coatings were investigated by using optical microscopy (OM), scanning electron microscopy (SEM), X-ray diffraction (XRD), microhardness, and electrochemical measurements. The results showed that increasing laser scanning speed promotes the transformation from planar crystals to dendrites and refines the grains concurrently. The γ-(Ni, Fe), FeNi3, and M23(C,B)6 are identified as the primary phase composition in the Ni45 coatings regardless of the laser scanning speed. Thereinto, the formation and growth of M23(C,B)6 precipitates can be inhibited with increasing laser scanning speed due to the higher cooling rate, which affects the microhardness distribution and corrosion resistance of the coating. On the one hand, the microhardness of the whole coating presents a downtrend with increasing laser scanning speed due to the reduction of M23(C,B)6 phase. On the other hand, the corrosion resistance in 0.5 M NaCl solution is improved to some extent at higher laser scanning speed because the less precipitation of M23(C,B)6 reduces the depletion of Cr around the precipitates. In contrast, all the coatings exhibit undifferentiated but poor corrosion resistance in the highly corrosive 0.5 M NaCl + 0.5 M H2SO4 solution.